2018
DOI: 10.5734/jgm.2018.15.2.55
|View full text |Cite
|
Sign up to set email alerts
|

Integrated diagnostic approach of pediatric neuromuscular disorders

Abstract: Clinical and genetic heterogeneity in association with overlapping spectrum is characteristic in pediatric neuromuscular disorders, which makes confirmative diagnosis difficult and time consuming. Considering evolution of molecular genetic diagnosis and resultant upcoming genetically modifiable therapeutic options, rapid and cost-effective genetic testing should be applied in conjunction with existing diagnostic methods of clinical examinations, laboratory tests, electrophysiologic studies and pathologic studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Over the past decade, clinical evaluation for NMDs has increasingly incorporated molecular genetics as a first or second tier diagnostic practice (Lee & Lee, 2018; McDonald, 2012). Options for single gene, multigene, and whole exome sequencing (WES) are now utilized by genetic specialists and neurologists.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, clinical evaluation for NMDs has increasingly incorporated molecular genetics as a first or second tier diagnostic practice (Lee & Lee, 2018; McDonald, 2012). Options for single gene, multigene, and whole exome sequencing (WES) are now utilized by genetic specialists and neurologists.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Accurate diagnosis is challenging and requires a multidisciplinary approach with interplay of signs, symptoms, laboratory tests, electrophysiological studies such as EMG, elaborate histopathology, immunohistochemistry and imaging studies. [4] Careful consideration of this information should be given prior to genetic testing, especially due to cost and difficulty in interpretation of the study result. So far, it is reported that the diagnostic yield of genetic tests varies from 18-60% depending on the disease subtype as per literature.…”
Section: Introductionmentioning
confidence: 99%
“…So far, it is reported that the diagnostic yield of genetic tests varies from 18-60% depending on the disease subtype as per literature. [4,5] Many variants of unknown significance are found, making the road to accurate diagnosis even more complicated.…”
Section: Introductionmentioning
confidence: 99%